Am i dyslexic? Parental self-report of literacy difficulties - Leavett, R; Nash, H; Snowling, M (John Wiley and Sons Ltd, 2014)
In the absence of criteria for the diagnosis of dyslexia, considerable weight is given to self-report, in particular in studies of children at family risk of dyslexia. The present paper uses secondary data from a previous study to compare parents who self-report as dyslexic and those who do not, in relation to objectively determined levels of ability. In general, adults are more likely to self-report as 'dyslexic' if they have poorer reading and spelling skills and also if there is a discrepancy between IQ and measured literacy. However, parents of higher social status who have mild literacy difficulties are more likely to self-report as dyslexic than parents who have weaker literacy skills but are less socially advantaged. Together the findings suggest that the judgement as to whether or not a parent considers themselves 'dyslexic' is made relative to others in the same social sphere. Those who are socially disadvantaged may, in turn, be less likely to seek support for their children. Â